2021
DOI: 10.5194/hess-2021-204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of ecosystem adaptation on hydrological model predictions in response to climate change

Abstract: Abstract. To predict future hydrological behavior in a changing world, often use is made of models calibrated on past observations, disregarding that hydrological systems, hence model parameters, will change as well. Yet, ecosystems likely adjust their root-zone storage capacity, which is the key parameter of any hydrological system, in response to climate change. In addition, other species might become dominant, both under natural and anthropogenic influence. In this study, we propose a top-down approach, whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Rakovec, Kumar, Mai, et al (2016) found ‘that constraining the model against streamflow only may be necessary but not sufficient to warrant the model fidelity for other complementary variables’. This so‐called equifinality problem is undesirable when models are used to make predictions under scenarios in which baseline drivers have shifted (non‐stationary behaviour, due to, for example, climate change or land use, as detailed by Bouaziz et al (2021)), and when accurate inferences of internal parameters or state variables are important (Anderton et al, 2002; Bouaziz et al, 2020; Heppner et al, 2007; Hrachowitz & Clark, 2017). Multiple criteria analysis, or MCA, has emerged as a useful tool which can help to reduce parameter uncertainty in hydrologic models and potentially improve accuracy of multiple model results.…”
Section: Introductionmentioning
confidence: 99%
“…Rakovec, Kumar, Mai, et al (2016) found ‘that constraining the model against streamflow only may be necessary but not sufficient to warrant the model fidelity for other complementary variables’. This so‐called equifinality problem is undesirable when models are used to make predictions under scenarios in which baseline drivers have shifted (non‐stationary behaviour, due to, for example, climate change or land use, as detailed by Bouaziz et al (2021)), and when accurate inferences of internal parameters or state variables are important (Anderton et al, 2002; Bouaziz et al, 2020; Heppner et al, 2007; Hrachowitz & Clark, 2017). Multiple criteria analysis, or MCA, has emerged as a useful tool which can help to reduce parameter uncertainty in hydrologic models and potentially improve accuracy of multiple model results.…”
Section: Introductionmentioning
confidence: 99%